Implementation of the Kurikulum Merdeka in Improving the Critical Thinking Ability of Class IV Students at SD Negeri 14 Belanti Barat - Arryal Syaputra; Rica Azwar; Nofriza Efendi; Gingga Prananda (The Future of Education Journal, 2024)
The purpose of this research is to determine the implementation of the Merdeka Curriculum in improving the critical thinking abilities of Grade IV students at SD Negeri 14 Belanti Barat. The Merdeka Curriculum is a curriculum with diverse intracurricular learning where the content will be more extensive so that students have enough time to explore concepts and strengthen competencies. This research uses qualitative methods by taking the object of SD Negeri 14 Belanti Barat. Data collection techniques are carried out through observation, interviews and documentation. Respondents in this research were the principal, class teacher and class IV students. The results of this research show that the implementation of learning for grade IV students using the Independent Curriculum has been implemented well and is supported by the school. Students have different critical thinking abilities. With differentiated learning in the independent curriculum, students' critical thinking abilities can increase. Then the obstacles found were that teachers did not receive enough training, and some teachers did not follow technological developments